Factors that Affect the Consumption Behavior of Halal Products among Muslims (Case Study of Sharia Banking Study Program) - Septiara Dwi Mariska; Riyan Pradesyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Religious awareness is an important dimension in an individual's life that can influence various aspects of behavior, including in consumption decisions. Students of the Sharia Banking Study Program are an interesting group to conduct research on how they behave when using halal goods. Many internal and external factors can affect the way they consume a product. Religiosity encourages buyers to prioritize halal products as part of their religious practices. However, without adequate halal literacy, a person may have difficulty ensuring the halalness of products, especially modern products with complex ingredients. The purpose of this research is to determine the influence of religiosity, halal product literacy and analyze the simultaneous influence of religiosity and halal product literacy on halal product consumption behavior among UMSU sharia banking study program students. In this study, the researcher used a quantitative research method. In this approach, data is collected through standardized instruments, such as questionnaires, which are designed to measure the level of influence of consumption behavior on halal products. Furthermore, the data obtained was analyzed using statistical techniques to test the hypothesis that had been formulated. There are 3 variables to be studied, the free variable (X1) is religiosity and (X2) halal literacy, while the bound variable (Y) is consumption behavior. The results of the study showed a determination value of 0.42. This means that 42.4% have the influence of religiosity on the consumption behavior of halal products, then there is also the influence of halal literacy on the consumption behavior of halal products, while together religiosity and halal literacy have an effect on the consumption behavior of halal products.